Below Water Table Mining, Pit Lake Formation, and Management Considerations for the Pilbara Mining Region of Western Australia - Cherie D. McCullough (Mining)
Located in northern Western Australia, the Pilbara is the highest productivity region for iron ore and other metal mining in Australia. As elsewhere, mine closure guidelines typically require post-closure landforms to be safe, stable, non-polluting and sustainable here in the long-term. I reviewed the primary literature, including international, national and state government guidelines and regional case studies for mine closure and related socio-environmental topics, to understand the key risks and management strategies needed to achieve these broad expectations for below water table (BWT) mining. Many BWT open cut mining projects will result in pit lakes in this region, many of which will be very large and will degrade in water quality with increasing salinisation over time. As an arid region, risks are dominated by alterations to hydrology and hydrogeology of largely unmodified natural waterways and freshwater aquifers. Although remote, social risks may also present, especially in terms of impacts to groundwater values. This remoteness also decreases the potential for realising practicable development of post-mining land uses for pit lakes. Explicitly considered risk-based decisions should determine closure outcomes for BWT voids, and when pit backfill to prevent pit lake formation will be warranted. However, maintaining an open pit lake or backfilling a void should also be considered against the balance of potential risks and opportunities.